Synthesis of Fulvic Acid-Coated Magnetite (Fe3O4–FA) and Its Application for the Reductive Adsorption of [AuCl4]– - Philip Anggo Krisbiantoro; Sri Juari Santosa; Eko Sri Kunarti (Universitas Gadjah Mada, 2017)
Fulvic acid-coated magnetite (Fe3O4–FA) has been synthesized through coprecipitation method using NH4OH. Synthesis conducted by cheap and environmentally friendly preparation used iron salts and extracted fulvic acid (FA) from Peat soil of Rawa Pening, Central Java, Indonesia. Characterization using FT–IR indicated that the coating of FA on Fe3O4 occurred through the formation of chemical bond between iron of Fe3O4 and carboxyl group of FA. The XRD measurement indicated that coated Fe3O4 successfully dispersed in smaller size than uncoated Fe3O4, i.e. from 16.67 to 14.84 nm for Fe3O4 and Fe3O4–FA, respectively. Synthesized Fe3O4–FA has pHPZC 6.37 and stable at pH > 3.0. The extracted FA has total acidity 866.61 cmol kg–1, –COOH content 229.77 cmol kg–1 and –OH content 636.84 cmol kg–1. Fe3O4–FA has total acidity 494.86 cmol kg–1, –COOH content 67.80 cmol kg–1 and –OH content 427.06 cmol kg–1. The adsorption rate constant (k) of [AuCl4]– on Fe3O4–A according to the Ho kinetic model was 8006.53 g mol–1 min–1. The adsorption capacity (qmax) according to Langmuir isotherm model was 1.24 × 10–4 mol g–1. The presence of reduction towards the adsorbed [AuCl4]– was shown by the appearance of peaks at 2θ: 37.41; 43.66; 64.25, and 76.67° in the XRD diffractogram.